Genetic Analysis of Abnormally High Ground Temperature From the Existence of Magmatic Rock Beneath Pingdingshan Coalfield - Wang, Qi; Liao, Jiajia; Zhou, Dongxu; Hou, Quanlin; Wang, Xinyi (Frontiers in Earth Science, 2022)
Studies on the genetic mechanisms of abnormally high ground temperatures in coalfields are of great significance for the efficient mining of coal mines and the development and utilization of geothermal water. Therefore, we measured the temperature of 45 Cambrian limestone groundwater samples, thermal conductivity values of 11 Cambrian limestone samples, and the contents of uranium, thorium, and potassium-40 of 40 rock samples, aiming to ascertain the heat source of the abnormally high ground temperature in the Pingdingshan coalfield. The results show that the average geothermal gradient in the coalfield is about 3.32 °C/100 m, and the calculated values of the average ground heat flow are about 104.28 mW/m2, which demonstrate the abnormally high ground temperature in Pingdingshan coalfield. We also concluded that the whole radiogenic heat generation in sedimentary and magmatic rocks is 1.53 mW/m2, whose contribution rate to the local geothermal flow is only 1.47 %. Hence, we can infer that magmatic rocks exposed in or near the coalfield area may supply the heat source for the abnormally high ground temperature beneath Pingdingshan coalfield. A comprehensive analysis further shows that the latest intrusion time of the magmatic rock mass in the coalfield was 35 Ma; its lava temperature was 900 °C, its cooling rate is 20.0 ℃/Ma, and the calculated residual temperature is more than 200.0 ℃. These values support the idea that the magmatic rocks may be the primary cause of the abnormally high ground temperature in the Pingdingshan coalfield.